(untitled) (Revista Direitos Humanos e Democracia, 2025)
In recent decades, the interdisciplinarity between critical theory, literature, and cultural studies has established itself as a fertile field of research for the debate on the body, gender, and power relations in contemporary society. This article proposes an in-depth analysis of the possibility of interposing discourses from different literary genres, articulated from a statement and a real, historically situated context. We take a comparative and intertextual look that brings together the theoretical contributions of Michel Foucault, especially in the relationship between knowledge and power, with the work of Virginia Woolf, whose texturality and subversion of gender paradigms gain momentum in the narrative of Orlando. The methodology took into account qualitative bibliographic research, documentary analysis, and comparative analysis of the representativeness of the precursors of the study of the transsexual body in the figures of Lili Elbe, Christine Jorgensen, at the international level, Valdirene, in the Brazilian context, and the character Orlando, a literary narrative by Virginia Woolf. We can understand that in the 1920s, Woolf understood the barriers and difficulties that transgender people faced and would face over the years, where fiction represents the reality experienced.